A gel composite material, a hydrovoltaic power generation device, and a preparation method and application thereof
By using a combination of hydrophobic insulated porous materials and ionic temperature-sensitive hydrogels in hydrovoltaic power generation devices, the problem of low heat transfer efficiency of traditional hydrovoltaic power generation devices is solved, and high-efficiency seawater evaporation and high-power hydrovoltaic power generation are achieved. Efficient desalination of seawater and new energy development in multiple scenarios.
Patent Information
- Application Number
- CN202411263579.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Traditional hydrovoltaic power generation devices are mostly two-dimensional structures, with low heat transfer efficiency and large heat loss, and cannot achieve high evaporation efficiency, high power collection and universal applications at the same time, which limits their application in the field of efficient desalination of seawater in multiple scenarios.
Hydrophobic insulating porous material is used as a skeleton to fill the ionic temperature-sensitive hydrogel, and combined with photothermal function fillers to form a gel composite material with a respiration effect. The material displays different hydrophobic or hydrophilic characteristics under different temperatures and light conditions, achieving synchronization of seawater evaporation and electrical energy output.
It has achieved efficient seawater evaporation and high-power hydrovoltaic power generation, high evaporation/desalination efficiency and all-weather power output capabilities, and expanded the application fields of seawater desalination and new energy development.
Smart Images

Figure CN118895015B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional gel materials, and in particular relates to a gel composite material, a hydrovoltaic power generation device, and a preparation method and application thereof. Background Art
[0002] Hydrovoltaic power generation devices have the characteristics of miniaturization, low cost, high evaporation efficiency and high adaptability. They can realize energy acquisition, clean water collection and self-powered equipment application in seawater environment and other sewage scenarios. They are one of the important directions for the development of seawater desalination. Developing high-efficiency hydrovoltaic power generation devices to achieve efficient desalination of seawater is of great significance to the sustainable development of the global water environment. The development and application of new hydrovoltaic power generation devices are conducive to promoting the active acquisition of environmental energy and the utilization and collection of solar energy, and are of great significance to the development and utilization of new energy, recycling and environmental sustainable development. However, traditional hydrovoltaic power generation devices are mostly two-dimensional structures with low heat transfer efficiency and large heat loss. They can usually only achieve electrical energy output under lighting conditions, especially unable to achieve high evaporation efficiency, high electrical energy collection and universal application at the same time, which greatly limits their application in the field of efficient seawater desalination in multiple scenarios. Research on hydrovoltaic power generation devices that can output electrical energy synchronously, autonomously absorb solar energy and convert it into thermal energy, realize solar energy interface evaporation and high-power hydrovoltaic power generation in multiple scenarios, is of great significance to the efficient desalination of seawater, alleviate the crisis of traditional mineral energy and expand the field of new energy. Summary of the invention
[0003] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a gel composite material, a hydrovoltaic power generation device and a preparation method and application thereof.
[0004] The present invention provides a gel composite material, characterized in that the gel composite material uses a hydrophobic insulating porous material as a skeleton, and the skeleton is filled with an ionic thermosensitive hydrogel; wherein the ionic thermosensitive hydrogel is a hydrogel modified with anionic groups or cationic groups; wherein the hydrogel modified with anionic groups or cationic groups is a crosslinked hydrogel of a cationic modifier or an anionic modifier and a matrix material, and the mass ratio of the matrix material to the ionic modifier in the ionic thermosensitive hydrogel is 10:1~1:1;
[0005] The matrix material includes one or more of poly N-isopropylacrylamide PNIPAM, poly N-vinylcaprolactam PNVCL, polysebacic anhydride PSPA, and poly N-acryloylglycineamide PNAGA; the anion modifier includes at least one of 2-acrylamido-2-methylpropane sulfonic acid AMPS and dimethylaminoethyl methacrylate DMAEMA; the cationic modifier includes at least one of (3-acrylamidopropyl)trimethylammonium chloride MPTAmC and dimethylaminopropylacrylamide DMAPAA.
[0006] The hydrophobic insulating material possesses hydrophobic or water-repelling properties.
[0007] The ionic thermosensitive hydrogel is a hydrogel with different wettability at different temperatures.
[0008] The ionic thermosensitive hydrogel has different hydrophobic or hydrophilic properties under different temperature conditions. The ionic hydrogel shows different hydrophobic or hydrophilic properties under different temperature conditions. Under light conditions, the upper and lower surfaces show different wettabilities, and water is continuously pumped from the bottom to the upper surface, showing a breathing effect similar to that of plant branches.
[0009] In the process of preparing thermosensitive hydrogel, an appropriate proportion of anion / cation modifier monomers is introduced to form ionic thermosensitive hydrogel, which improves the internal ion selectivity of hydrogel. During the evaporation of seawater, the ionic groups can enhance the electrostatic water capture capacity, promote the efficient transmission of water and improve the efficiency of seawater desalination. At the same time, the ionic groups can promote the separation of anions and cations in water and improve the power generation efficiency of hydrovoltaic power generation devices.
[0010] Preferably, the hydrophobic insulating porous material has vertically penetrating internal pores.
[0011] Preferably, the hydrophobic insulating porous material is a hydrophobic insulating porous material having a photothermal conversion function.
[0012] Preferably, the hydrophobic insulating porous material having a photothermal conversion function comprises: a hydrophobic insulating porous material containing a photothermal functional filler or an intrinsic black hydrophobic insulating porous material without a photothermal functional filler.
[0013] Furthermore, the mass percentage of the photothermal functional filler in the hydrophobic insulating porous material containing the photothermal functional filler is 1wt%~10wt%.
[0014] Preferably, the photothermal functional filler includes one or more of carbon powder, carbon black, carbon nanotubes, graphene, graphite, amorphous carbon, MXene, metal organic framework MOF, and azobenzene. The functional filler converts light energy into heat energy to provide heat energy for seawater evaporation.
[0015] Preferably, the hydrophobic insulating porous material containing photothermal functional fillers includes: one or more of aerogel, foam plastic, and porous wood containing photothermal functional fillers;
[0016] The aerogel is one or more of unmodified aerogel, hydrophobic and / or insulating modified aerogel; the foam plastic is one or more of unmodified foam plastic, hydrophobic and / or insulating modified foam plastic; the porous wood is one or more of unmodified porous wood, hydrophobic and / or insulating modified porous wood.
[0017] Furthermore, the aerogel is at least one of an inorganic aerogel, an organic aerogel, and an organic / inorganic aerogel composite material; wherein the inorganic aerogel includes one or more of TiO2 aerogel, SiO2 aerogel, and SiC fiber aerogel; the organic aerogel includes one or more of TEMPO oxidized cellulose aerogel TCNF, microcrystalline cellulose aerogel, polyvinylidene fluoride aerogel, polyacrylonitrile aerogel, and poly(vinylidene fluoride-co-hexafluoropropylene) aerogel; the organic / inorganic aerogel composite material includes one or more of TCNF / MXene aerogel, ethyl cellulose / Fe3O4 aerogel, and TCNF / TiO2 aerogel.
[0018] Preferably, the foam plastic is one or more of polystyrene foam plastic, polypropylene foam plastic, polyethylene foam plastic, polycarbonate foam plastic, polytetrafluoroethylene foam plastic, polyvinyl chloride foam plastic, polyamide foam plastic, polyurethane foam plastic, polyester foam plastic, phenolic resin foam plastic, epoxy resin foam plastic, and polyvinyl alcohol foam plastic; the porous wood is one or more of intrinsically hydrophobic modified wood, physically modified porous wood, and chemically modified porous wood; the wood includes one or more of poplar, willow, paulownia, sycamore, birch, red pine, and grass.
[0019] Preferably, the intrinsic black hydrophobic insulating porous material containing no photothermal functional filler comprises one or more of foam plastics and porous wood containing no photothermal functional filler; wherein the foam plastic is one or more of unmodified foam plastics and foam plastics modified by hydrophobicity and / or insulation; and the porous wood is one or more of unmodified porous wood and porous wood modified by hydrophobicity and / or insulation.
[0020] Preferably, the foam plastic is one or more of polystyrene foam plastic, polypropylene foam plastic, polyethylene foam plastic, polycarbonate foam plastic, polytetrafluoroethylene foam plastic, polyvinyl chloride foam plastic, polyamide foam plastic, polyurethane foam plastic, polyester foam plastic, phenolic resin foam plastic, epoxy resin foam plastic, polyvinyl alcohol foam plastic. Preferably, the porous wood is one or more of intrinsically hydrophobic modified wood, physically modified porous wood, and chemically modified porous wood; wherein the wood includes one or more of poplar, willow, paulownia, sycamore, birch, red pine, and grass.
[0021] Preferably, the hydrophobic modification is one or more of surface micro-nano structure construction and surface hydrophobic coating processing; wherein the surface micro-nano structure construction method includes one or more of corrosion, etching, sol-gel method, and laser printing; the surface hydrophobic coating processing includes one or more of surface coating and immersion treatment; the material used for the surface hydrophobic coating processing includes one or more of fluorine-containing coatings (such as 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane, perfluorodecyltriethoxysilane), silicon-containing coatings (such as methyltrimethoxysilane, hexadecyltrimethoxysilane, vinyltrimethoxysilane), and fat chain-containing coatings (such as polylactic acid, hexadecyltrimethoxysilane).
[0022] Preferably, the insulation modification is one or more of surface insulation treatment and impregnation insulation treatment; the material used for the insulation modification is at least one of organic insulation material, inorganic insulation material, and organic / inorganic composite insulation material;
[0023] Preferably, the organic insulating material is one or more of silicone resin, phenolic resin, epoxy resin, and polyimide; the inorganic insulating material is one or more of phosphate, silicate, TiO2, Cr2O3, MgO, ZrO2, SiO2, and Al2O3; the composite insulating material is one or more of SrTiO3 modified resin, SiO2 / SiC modified resin, Fe3O4 / SiO2 modified resin, and SiO2 modified resin.
[0024] Further preferably, the aerogel is polyvinylidene fluoride aerogel. Polyvinylidene fluoride is a chemically stable material that can withstand a variety of corrosive environments such as acid and alkali. It has a wide range of application potential in seawater desalination. Aerogel is a material with a three-dimensional pore structure, a relatively low density and excellent mechanical properties, and is therefore widely used in water purification. Polyvinylidene fluoride aerogel can maintain its original porous structure in a high temperature environment. The aerogel material has basically no shrinkage, high strength, and stable porosity and specific surface area. Due to the porous structure of the aerogel, its water absorption rate is very high, and even in a strong acid and alkali environment, its service life is basically not affected by the shortening. Polyvinylidene fluoride itself has electronegativity, which can promote the separation of anions and cations in water during the desalination process, generate an electric potential energy difference, and realize hydrovoltaic power generation.
[0025] The aerogel preparation method is one or more of the following: sol-gel method, inorganic aluminum salt method, rapid gel method, template method, emulsion method, impregnation method, chemical vapor deposition method, three-dimensional printing method, phase exchange method, carbon thermal reduction reaction method, and the aerogel is obtained by drying. The drying method is supercritical drying, subcritical drying, freeze drying, vacuum drying, atmospheric pressure drying, conduction drying, and distillation drying.
[0026] Preferably, the aerogel preparation method is a phase exchange method. The solvent used for the aerogel is dimethyl sulfoxide (DMSO), and the proportion of polyvinylidene fluoride is 3wt%~30wt%. Polyvinylidene fluoride can be dissolved in dimethyl sulfoxide. Since the solidification point of dimethyl sulfoxide is 18.25℃. And water is a non-solute of the polyvinylidene fluoride solution, the polyvinylidene fluoride solution can be phase exchanged in a water environment of 0℃~18.25℃, and the solidified dimethyl sulfoxide is exchanged for water, and then dried.
[0027] The drying method is supercritical drying or freeze drying.
[0028] More preferably, the aerogel adopts a unidirectional freeze-drying method, pouring the solvent into a bottom metal mold and freezing it in a liquid nitrogen environment. The solution will first crystallize at the bottom, and the ice crystals will grow upward through the vertical temperature gradient difference to form vertically penetrating apertures, thereby improving the long-term salt resistance of the hydrovoltaic power generation device and meeting the requirements of long-term application. Preparation of gel composite materials: The hydrogel solution is pumped into the material through a vacuum pump, and the hydrogel solution reacts inside the aerogel to form a hydrogel.
[0029] For example, polyvinylidene fluoride aerogel containing photothermal functional filler: a DMSO solution containing polyvinylidene fluoride and the raw materials of photothermal functional filler are obtained by directional freezing.
[0030] The present invention provides a method for preparing a gel composite material, comprising:
[0031] (1) mixing a base monomer, a cross-linking agent, an initiator, a modifier, and a solvent to obtain a mixed solution;
[0032] (2) The hydrophobic insulating porous material is immersed in the mixed solution, vacuum filtered, cooled, and then immersed in the catalyst solution under protective gas conditions for cross-linking to obtain a gel composite material.
[0033] Preferably, in step (1), the matrix monomer is one or more of N-isopropylacrylamide NIPAM, N-vinylcaprolactam NVCL, sebacic anhydride SPA, and N-acryloylglycineamide NAGA; the crosslinking agent is N,N-methylenebisacrylamide MBAA; the initiator is ammonium persulfate APS; and the solvent is deionized water;
[0034] In the mixed solution of step (1), the monomer accounts for 3wt% to 10wt% of the solvent by mass, the cross-linking agent accounts for 0.01wt% to 0.1wt% of the solvent by mass, the initiator accounts for 0.1wt% to 1wt% of the solvent by mass; and the modifier accounts for 0.3wt% to 10wt% of the solvent by mass;
[0035] The cross-linking time in step (2) is 5-12 hours.
[0036] Preferably, in step (2), the temperature is cooled to 2-8° C.; the protective gas is nitrogen; the catalyst is tetramethylethylenediamine (TEDMA); and the concentration of the catalyst solution is 0.5wt%-1wt%.
[0037] The present invention provides a hydrovoltaic power generation device, which comprises any of the above-mentioned gel composite materials or a gel composite material prepared by any of the above-mentioned methods for preparing the gel composite materials and an electrode.
[0038] The electrodes include a positive electrode and a negative electrode; the electrodes are respectively arranged on the upper and lower sides of the gel composite material; wherein the positive electrode and the negative electrode are arranged in parallel;
[0039] The electrode material is a porous electrode; wherein the porous electrode is a metal foam electrode or a graphite felt electrode; wherein the metal foam electrode comprises one or more of a foam copper electrode, a foam stainless steel electrode, a foam iron-nickel electrode, a foam nickel electrode, a foam titanium electrode, and a foam aluminum electrode;
[0040] Further preferably, the metal foam electrodes are strip-shaped copper foam electrodes, and the electrodes are respectively embedded in different positions in the vertical direction of the material to collect hydroelectric energy generated by the separation of positive and negative ions in the solution.
[0041] Preferably, the electrodes are spaced 0.5 cm to 10 cm apart and are built into the upper and lower parts of the gel composite material to collect the electrical energy generated by the separation of seawater ions.
[0042] Further preferably, the foam metal electrode is a strip-shaped foam copper electrode, and the distance between the upper and lower electrodes is 1 cm-10 cm.
[0043] The electrodes are connected to an external energy collection device via wires.
[0044] The hydrovoltaic power generation device continuously outputs electrical energy during the evaporation process of the water body to supply electrical appliances.
[0045] The hydrovoltaic power generation device is designed and formed based on a gel composite material, and achieves differential output of electrical energy under different solutions and different environmental conditions.
[0046] The hydrovoltaic power generation device continuously outputs electrical energy during the evaporation of seawater for use by electrical appliances.
[0047] The water body evaporation function, wherein the water body is one or more of ultrapure water, distilled water, deionized water, tap water, river water, lake water, sea water, rainwater, industrial wastewater, domestic sewage, and agricultural wastewater; the hydrovoltaic power generation is the electrostatic energy generated by the separation of positive and negative ions in the solution.
[0048] The hydrovoltaic power generation device can realize the evaporation and desalination of seawater and generate hydrovoltaic electrical energy output at the same time.
[0049] The invention provides a method for preparing a hydrovoltaic power generation device, comprising: assembling electrodes on a gel composite material, or assembling electrodes in situ when preparing the gel composite material.
[0050] Specifically, the method comprises: mixing a matrix monomer, a cross-linking agent, an initiator, a modifier and a solvent to obtain a mixed solution; immersing a hydrophobic insulating porous material in the mixed solution, vacuum filtering, cooling, and then immersing the mixed solution in a catalyst solution under protective gas conditions for cross-linking for 5-12 hours to obtain a gel composite material, assembling electrodes, and obtaining a hydrovoltaic power generation device;
[0051] Or the matrix monomer, crosslinking agent, initiator, modifier and solvent are mixed to obtain a mixed solution; the hydrophobic insulating porous material equipped with electrodes is immersed in the mixed solution, vacuum filtered, cooled, and then immersed in a catalyst solution under protective gas conditions for crosslinking for 5-12 hours to obtain a hydrovoltaic power generation device.
[0052] The present invention provides an application of the hydrovoltaic power generation device or the hydrovoltaic power generation device prepared by the preparation method of the hydrovoltaic power generation device in the fields of environment, new energy and renewable resources.
[0053] Preferably, the application in the environmental field includes one or more of seawater desalination, sewage treatment, distilled water collection, and plant bionic materials;
[0054] The new energy field includes one or more of solar power generation and hydroelectric power generation;
[0055] The renewable resource field includes one or more of plant growth monitoring, ecosystem services, ecosystem restoration, and water energy collection.
[0056] The present invention develops a hydrovoltaic power generation device with a breathing effect, which can simultaneously meet the requirements of high-power power generation, high evaporation efficiency and long-term practicality, and is expected to achieve efficient utilization of solar energy and seawater resources. The hydrovoltaic power generation device has an intrinsic photothermal transpiration effect, can convert solar energy into thermal energy, and has an ionic group-enhanced hydrovoltaic power generation capacity, can achieve autonomous power generation through the separation of positive and negative charges in water, output electrical energy, and simultaneously achieve seawater evaporation and efficient desalination; the hydrovoltaic power generation device has the characteristics of universal materials, simple structure, easy processing and development, and multi-scenario application, and has huge application prospects in the field of new energy.
[0057] The present invention is a hydrovoltaic power generation device and application based on ion-thermosensitive hydrogel empowerment. The device is composed of a hydrophobic insulating porous material (photothermal functional filler), an ion-thermosensitive hydrogel with a breathing effect filled in the pore, and an electrode; specifically, the porous material has a photothermal conversion function, which can form a temperature gradient difference between the upper and lower parts of the material to drive water evaporation; the thermosensitive hydrogel filled in the porous material can directionally regulate the wettability of the pore size. Under light conditions, the thermosensitive hydrogel close to the upper surface shrinks due to heat, and the hydrophilicity decreases, prompting the porous material to form an upper and lower gradient wettability, achieving a self-transport effect similar to the water in the trunk conduit, and promoting water evaporation and export. Ion modification makes the porous material have ion selectivity inside and obtains a stronger water absorption and water capture ability. Compared with ion-doped hydrogels, ion-modified hydrogels are more stable, and can realize that the device has the ability to generate electricity autonomously under light or dark conditions, and can maintain a long-term stable output, which greatly improves the efficiency of seawater evaporation and all-weather power output efficiency. The present invention realizes for the first time the hydrophobic insulating porous material empowered by ion-sensitive hydrogel, realizing seawater evaporation, desalination and synchronous power generation, that is, converting the ionic chemical energy in the solution into electrical energy during the seawater desalination process, and its electrical output can be stored or used to power electrical appliances, greatly expanding the application in fields such as seawater desalination and new energy development.
[0058] Beneficial Effects
[0059] Compared with the prior art, the present invention adopts a combination of hydrophobic insulating porous materials and functional thermosensitive hydrogels, which can simultaneously realize seawater desalination and hydrovoltaic power generation. For example, the photothermal filler in the porous material can use the physical light-heat transfer effect to achieve rapid heat accumulation on the upper surface of the material, forming an upper and lower heat gradient to drive water evaporation; the thermosensitive hydrogel embedded in the porous material can use its wettability difference at different temperatures to achieve gradient wettability on the upper and lower surfaces of the material, further directionally control the pore size change, and realize a water transfer function similar to that of a tree trunk duct; the introduction of ionic segments in the thermosensitive hydrogel gives the hydrogel ion selectivity, enabling use in multiple scenarios, and improving the power generation of the device and the performance stability of long-term use. Compared with other hydrovoltaic power generation devices, the present invention adopts low-cost, simple formulas and assembly technologies to achieve high evaporation / desalination efficiency of hydrovoltaic power generation devices and high-power DC output of hydrovoltaic power generation.
[0060] According to the research results of the present invention, the seawater evaporation rate of the developed hydrovoltaic power generation device can reach up to 2.75kg / (m 2 *h). Based on this effect, the present invention also provides that the hydrovoltaic power generation device can achieve DC power acquisition during the seawater evaporation / desalination process.
[0061] The present invention discloses a hydrovoltaic power generation device that can provide hydrovoltaic power generation, and its preparation method and application. The evaporator is based on hydrophobic insulating photothermal porous materials and ion temperature-sensitive hydrogel wettability regulation. It has a high-efficiency photothermal conversion effect and positive and negative ion separation capabilities, and can form a temperature and wettability gradient of the material, promote water evaporation and ion separation, and simultaneously realize seawater desalination and hydrovoltaic power generation, and collect electrical energy and desalinated water. The present invention integrates ion temperature-sensitive hydrogels into hydrophobic photothermal porous materials for the first time, and can simultaneously achieve synergistic capabilities such as efficient seawater desalination, hydrovoltaic power collection, and plant irrigation, greatly expanding the application of hydrovoltaic power generation devices in agriculture, new energy and other fields;
[0062] The high-efficiency hydrovoltaic power generation device provided by the present invention is simple to prepare, low in cost, has a wide range of applications, and has low requirements for materials, equipment, and the environment. It has high light-to-heat conversion efficiency, strong hydrovoltaic power generation, and great potential for large-scale production. Typically, the hydrovoltaic power generation device can output 23.33 uw / cm in seawater desalination. 2 Electricity. The collected fresh water can be used for agricultural irrigation, and the collected electricity can drive low-power electronic devices. It has important inspiration and driving effect on improving the efficiency of seawater evaporation and hydrovoltaic power generation, and promoting the construction and development of self-irrigation ecosystems. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is a physical picture of the PAN-PNIPAM-DMAEMA hydrovoltaic power generation device described in Example 1;
[0064] Figure 2 is a scanning electron microscope image of a cross section of the PAN-PNIPAM-DMAEMA hydrovoltaic power generation device described in Example 1;
[0065] Figure 3 The actual image and thermal image of the PNIPAM hydrogel of Example 1 changing with temperature;
[0066] Figure 4 is a graph showing the change in water evaporation mass over time of the PVDF-PNIPAM-AMPS hydrovoltaic power generation device described in Example 2 under 1.0 sun light intensity irradiation;
[0067] Figure 5 is a graph showing the change of interface evaporation temperature over time of the PVDF-PNIPAM-AMPS hydrovoltaic power generation device described in Example 2 under 1.0 sun light intensity irradiation;
[0068] Figure 6 This is the current-voltage curve of the PVDF-PNIPAM-AMPS hydrovoltaic power generation device described in Example 2 measured by an electrochemical workstation;
[0069] Figure 7is the hydrovoltaic power output of a single PNVCL-AMPS-wood hydrovoltaic power generation device described in Example 3;
[0070] Figure 8 is the hydrovoltaic power output of a single PNAGA-DMAEMA-EVA foam hydrovoltaic power generation device described in Example 4;
[0071] Fig. 9 is the hydrovoltaic power output of a single TCNF-DMAPAA-PSPA aerogel hydrovoltaic power generation device described in Example 5;
[0072] Fig.10 is the hydrovoltaic power output of a single PVDF-PNIPAM-MPTAmC aerogel hydrovoltaic power generation device described in Example 6;
[0073] Fig.11 is the hydrovoltaic power generation output of a single (PVDF-HFP)-NIPAM-AMPS hydrovoltaic generator described in Example 7 under different simulated water samples;
[0074] Fig.12 It is a comparison of the actual picture and ultraviolet spectrum of water quality before and after desalination of the microcrystalline-PNIPAM-AMPS hydrovoltaic power generation device described in Example 8. DETAILED DESCRIPTION
[0075] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0076] The raw materials used in the embodiment are as follows:
[0077] Polyacrylonitrile: from Shanghai Titan Technology Co., Ltd., model specification: RG, weight average molecular weight: 50000, item number: 013358765;
[0078] Dimethyl sulfoxide: from Shanghai Titan Technology Co., Ltd., model specification: AR, ≥99.0% (GC), product number: 01104495;
[0079] N-isopropylacrylamide: from Shanghai Aladdin Biochemical Technology Co., Ltd., model specification: 98%, item number: I106818-100g;
[0080] Carbon nanotubes: from Shanghai Aladdin Biochemical Technology Co., Ltd., model specification: >95%, outer diameter: 8-15nm, length: ~50μm, specific surface area>140m 2 / g, item number: C313046-5g;
[0081] Hexadecyltrimethoxysilane: from Shanghai Titan Technology Co., Ltd., model specification: RG, 98%+, item number: 01030566;
[0082] N, N-methylenebisacrylamide: from Shanghai Aladdin Biochemical Technology Co., Ltd., model specification: CP, 97%, item number: M104022-25g;
[0083] Foam metal electrode: from Chengnan Jinyihe New Materials Business Department of Wuzhong Economic Development Zone, model specification: 1.8*200*300mm;
[0084] Dimethylaminoethyl methacrylate: from Ron's reagent, model specification: 99.9% (GC), product number: R096935-500ml;
[0085] Tetramethylethylenediamine: from Shanghai MacLean Biochemical Technology Co., Ltd., model specification: 99%, item number: N818999-1L;
[0086] Polyvinylidene fluoride: from Shanghai Yuanye Biotechnology Co., Ltd., model specification: 5um, 99.9%, molecular weight 600,000, item number: S27372-500g;
[0087] 2-Acrylamide-2-methylpropanesulfonic acid: from Shanghai MacLean Biochemical Technology Co., Ltd., model specification: 98%, item number: A800508-100g;
[0088] Sodium chloride: from Sinopharm Chemical Reagent Co., Ltd., model specification: AR (Shanghai test), ≥99.5%, item number: 10019318
[0089] Amorphous carbon: from Shanghai MacLean Biochemical Technology Co., Ltd., model specification: 400 mesh, powder, product number: C829813-100g;
[0090] n-Dodecanethiol: from Shanghai MacLean Biochemical Technology Co., Ltd., model specification: 98%, item number: D806874-25ml;
[0091] N-vinyl caprolactam: from Shanghai MacLean Biochemical Technology Co., Ltd., model specification: 99%, item number: N838648-2g;
[0092] Vinyltrimethoxysilane: from Shanghai MacLean Biochemical Technology Co., Ltd., model specification: 98%, item number: V823925-25ml;
[0093] Ammonium persulfate: from Sinopharm Chemical Reagent Co., Ltd., model specification: AR (Shanghai test), ≥98.0%, item number: 10002616;
[0094] N-Acryloylglycinamide: from Shanghai Yuanye Biotechnology Co., Ltd., model specification: 98%, item number: Y69205-250mg;
[0095] TEMPO oxidized cellulose: from Beijing Shansi Technology Co., Ltd.;
[0096] Polydimethylsiloxane: from Shanghai MacLean Biochemical Technology Co., Ltd., product number: D849784;
[0097] 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane: from Sinopharm Chemical Reagent Co., Ltd., model specification: 97%, item number: XW785604591;
[0098] Graphene: from Sane Chemical Technology (Shanghai) Co., Ltd., model specifications: particle size: 7-12μm, number of layers: 1-3, 98%, item number: A62053;
[0099] Sebacic anhydride: from Sane Chemical Technology (Shanghai) Co., Ltd., model specification: 98%, product number: A010415;
[0100] Dimethylaminopropyl acrylamide: from Shanghai MacLean Biochemical Technology Co., Ltd., model specification: 98%, item number: N838796-5g;
[0101] (3-Acrylamidopropyl)trimethylammonium chloride: from Shanghai MacLean Biochemical Technology Co., Ltd., model specification: 74-76%, item number: A838630-5ml;
[0102] Poly(vinylidene fluoride-co-hexafluoropropylene): from Shanghai MacLean Biochemical Technology Co., Ltd., model specifications: weight average molecular weight: 400000, number average molecular weight: 130000, item number: P875306-1g;
[0103] Microcrystalline cellulose: from Shanghai MacLean Biochemical Technology Co., Ltd., model specification: 100-200 mesh, product number: M909921-100g;
[0104] Graphite powder: from Shanghai Aladdin Biochemical Technology Co., Ltd., model specification: 99.95%, ≥325 mesh, item number: G123645-100g.
[0105] Example 1
[0106] In this embodiment, a hydroelectric power generation device is provided, and the preparation method thereof is as follows:
[0107] Polyacrylonitrile (PAN) was dissolved in dimethyl sulfoxide to prepare a solution with a concentration of 6wt%, and 5wt% carbon nanotubes were added to the solution and stirred to obtain an aerogel solution. A 4cm×2cm foamed nickel electrode with a 2cm interval between the upper and lower electrodes was placed in a unidirectional frozen mold, the above sol was poured into the mold, and then liquid nitrogen was frozen for 1 h, exchanged in a deionized environment of 2-8℃ for 48h, and then freeze-dried for 48 h to obtain polyacrylonitrile (PAN) aerogel. The above polyacrylonitrile (PAN) aerogel was chemically vapor deposited (90℃, 5 h) using hexadecyltrimethoxysilane to obtain a hydrophobically modified polyacrylonitrile (PAN) aerogel; wherein the upper and lower parallel foamed nickel electrodes were spaced 2cm apart and embedded in the aerogel respectively, and the lower electrode and the bottom were spaced 2cm apart.
[0108] 5wt% N-isopropylacrylamide (NIPAM), 0.1wt% N,N-methylenebisacrylamide (MBAA), 0.5wt% ammonium persulfate (APS), and 0.5wt% dimethylaminoethyl methacrylate (DMAEMA) were dissolved in deionized water to prepare NIPAM-DMAEMA solution, and the aerogel was immersed in the solution, and the solution was vacuum filtered. The aerogel filled with the hydrogel solution was cooled to 2-8°C. In a nitrogen environment, the aerogel was immersed in a 0.6wt% tetramethylethylenediamine solution for crosslinking for 12h to crosslink the hydrogel inside the PAN aerogel in situ. PAN-PNIPAM-DMAEMA aerogel (named PAN-PD) was obtained. The foamed iron-nickel electrode was connected to an external energy collection device through a wire to record the electrostatic energy generated by the separation of positive and negative ions in the solution inside the hydrovoltaic power generation device.
[0109] like Figure 1 The figure shows the actual picture of the hydrovoltaic power generation device. Figure 2 This is a cross-sectional scanning electron microscope image of a hydrovoltaic power generation device. From the image, it can be seen that region 1 is a vertically penetrating aerogel channel, and region 2 is the dried hydrogel attached to the aerogel channel. Figure 3 This is a physical picture and thermal imaging of the change of PNIPAM hydrogel with temperature. The hydrogel undergoes a phase change when the temperature rises from 33 degrees to 41.4 degrees.
[0110] Example 2
[0111] In this embodiment, a hydrovoltaic power generation device is provided, and its preparation method is as follows: polyvinylidene fluoride (PVDF) is dissolved in dimethyl sulfoxide to prepare a solution with a concentration of 8wt%, 4wt% graphite powder is added to the solution, and aerogel solution is obtained after being stirred evenly. A 4cm×2cm foamed iron-nickel electrode with a 3cm interval between the upper and lower electrodes is placed in a one-way frozen mold, the above sol is poured into the mold, and then liquid nitrogen is frozen for 2h, exchanged in a deionized environment of 2-8℃ for 48h, and then freeze-dried for 48h to obtain polyvinylidene fluoride (PVDF) aerogel; wherein the upper and lower foamed iron-nickel electrodes arranged in parallel are spaced 3cm apart and are respectively embedded in the aerogel, and the lower electrode and the bottom are spaced 2cm apart.
[0112] 10wt% N-isopropylacrylamide (NIPAM), 0.05wt% N,N-methylenebisacrylamide (MBAA), 0.5wt% ammonium persulfate (APS), and 6wt% 2-acrylamide-2-methylpropanesulfonic acid (AMPS) were dissolved in deionized water to prepare NIPAM solution, and the aerogel was immersed in the NIPAM solution, and the above solution was vacuum filtered. The aerogel filled with the hydrogel solution was cooled to 2-8 degrees. In a nitrogen environment, the aerogel was immersed in a 0.5% tetramethylethylenediamine solution for cross-linking for 12 hours to cross-link the hydrogel internally. PVDF-PNIPAM-AMPS aerogel (named PPA) was obtained. The foamed iron-nickel electrode was connected to an external energy collection device through a wire to record the electrostatic energy generated by the separation of positive and negative ions in the solution inside the hydrovoltaic power generation device.
[0113] Figure 4 This is a curve showing the evaporation mass of the hydrovoltaic power generation device changing with time under 1.0 sun intensity. The maximum evaporation rate of seawater can reach 2.75 kg / (m 2 *h). Figure 5 The figure shows the curve of the interface evaporation temperature of the hydrovoltaic power generation device changing with time under 1.0 sun intensity irradiation. Within two minutes, the maximum surface temperature can reach 120 degrees in dry conditions and 42 degrees in wet conditions, that is, the hydrogel phase transition temperature can be reached in wet conditions.
[0114] In this embodiment, the water sample is a simulated seawater solution (3.5wt% NaCl), and the light source is 1.0sun simulated sunlight. Figure 6 This is the maximum power output of the hydrovoltaic power generation device after one hour of testing. The shaded area is the output power, which can output 23.33 uw / cm 2 Electricity.
[0115] Example 3
[0116] In this embodiment, a wood-based hydrovoltaic power generation device is provided, and its preparation method is as follows: a black porous wood board is processed into the shape of the polyvinylidene fluoride aerogel in Example 1, the porous wood board is soaked in a dodecanethiol ethanol solution (0.01 M) for 1 hour, and then the sample is dried in an oven (110 ° C, 2 hours) to obtain a hydrophobically modified wood board. 8wt% N-vinyl caprolactam (NVCL), 0.05wt% N,N-methylenebisacrylamide (MBAA), 0.5wt% ammonium persulfate (APS), and 1wt% 2-acrylamide-2-methylpropanesulfonic acid (AMPS) are dissolved in deionized water to prepare an NVCL-AMPS solution, and the porous wood board is soaked in a PNVCL solution, and the above solution is vacuum filtered. The above porous wood board filled with the hydrogel solution is cooled to 2-8 ° C. And in a nitrogen environment, the device is soaked in a 0.5wt% tetramethylethylenediamine solution for cross-linking for 12 hours, so that the internal hydrogel is cross-linked in situ to obtain PNVCL-wood. Foam stainless steel electrodes were embedded in porous wood, with the upper and lower parallel foam stainless steel electrodes spaced 4 cm apart and embedded in the wood respectively, with the lower electrode spaced 2 cm apart from the bottom. The foam stainless steel electrodes were connected to an external energy collection device through wires to record the electrostatic energy generated by the separation of positive and negative ions in the solution inside the hydrovoltaic power generation device.
[0117] In this embodiment, the water sample is a simulated seawater solution (3.5wt% NaCl), and the light source is 1.5sun simulated sunlight. Within 4 hours, the hydrovoltaic power generation device can generate a DC voltage output of about 0.1V. Figure 7 It is the hydrovoltaic electrical energy output of the single hydrovoltaic power generation device described in this example.
[0118] Example 4
[0119] In this embodiment, a foam-based hydrovoltaic power generation device is provided, and its preparation method is as follows: black EVA foam is processed into the shape of polyvinylidene fluoride aerogel in Example 1, and vinyl trimethoxysilane (VTMO) is used for chemical vapor deposition (90 ° C, 2 h) to obtain hydrophobically modified EVA foam. 8wt% N-acryloyl glycinamide (NAGA), 0.05wt% N, N-methylenebisacrylamide (MBAA), 0.5wt% ammonium persulfate (APS), and 7wt% dimethylaminoethyl methacrylate (DMAEMA) are dissolved in deionized water to prepare NAGA solution, and the porous wooden board is immersed in the PNAGA solution, and the above solution is vacuum filtered. The porous wooden board filled with the hydrogel solution is cooled to 2-8 ° C. And in a nitrogen environment, the device is immersed in a 0.6wt% tetramethylethylenediamine solution for cross-linking for 12 hours, so that the internal hydrogel is cross-linked in situ to obtain NAGA-EVA foam. The nickel foam electrode was embedded in the PNAGA-EVA foam, and the upper and lower nickel foam electrodes were set in parallel and embedded in the wood with a spacing of 5 cm, and the lower electrode was 2 cm away from the bottom. The nickel foam electrode was connected to an external energy collection device through a wire to record the electrostatic energy generated by the separation of positive and negative ions in the solution inside the hydrovoltaic power generation device.
[0120] In this embodiment, the water sample is a simulated seawater solution (3.5wt% NaCl), and the light source is 1.0sun simulated sunlight. Within 4 hours, the hydrovoltaic power generation device can generate a DC voltage output of about 0.3V. Figure 8 It is the hydrovoltaic electrical energy output of the single hydrovoltaic power generation device described in this example.
[0121] As shown in Figures 7-8, the voltage values in Examples 3 and 4 are "positive" values, both of which belong to anion-modified hydrogels. During the evaporation of seawater, the anion-modified hydrogels have electronegativity, which promotes the transport of cations and hinders the transport of anions. A large number of cations accumulate at the upper electrode, and a large number of anions accumulate at the lower electrode. During the test, the positive electrode of the external energy collection device is connected to the upper electrode, and the negative electrode is connected to the lower electrode, thereby generating a positive potential difference.
[0122] Example 5
[0123] In this embodiment, a cellulose-based hydrovoltaic power generation device is provided, and its preparation method is as follows: 3wt% graphene is dispersed in 1% TEMPO oxidized cellulose (TCNF) by mass fraction, the above sol is poured into a one-way freezing mold, 4cm×2cm foam copper electrodes are placed 7cm above and below the mold, and then liquid nitrogen freezing is performed for 1 hour, and then freeze-dried for 24 hours to obtain TCNF aerogel; wherein the upper and lower parallel foam iron-nickel electrodes are 7cm apart and embedded in the aerogel respectively, wherein the lower electrode and the bottom are 2cm apart. The aerogel is immersed in diluted polydimethylsiloxane (PDMS) for 2 minutes, taken out and solidified, and then the sample is chemically vapor deposited (80 ℃, 2 hours) with 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane (PFTOS) to obtain a hydrophobic TCNF aerogel (named TCPP). 8wt% sebacic anhydride (SPA), 0.05wt% N,N-methylenebisacrylamide (MBAA), 0.5wt% ammonium persulfate (APS), and 10wt% dimethylaminopropyl acrylamide (DMAPAA) were dissolved in deionized water to prepare PSPA solution, and the cellulose aerogel was immersed in the SPA solution, and the above solution was vacuum filtered. The cellulose aerogel filled with the hydrogel solution was cooled to 2-8°C. Under a nitrogen environment, the device was immersed in a 0.55wt% tetramethylethylenediamine solution for cross-linking for 12h to cross-link the internal hydrogel in situ to obtain TCNF-PSPA aerogel. The foam copper electrode was connected to an external energy collection device through a wire to record the electrostatic energy generated by the separation of positive and negative ions in the solution inside the hydrovoltaic power generation device.
[0124] In this embodiment, the water sample is a simulated seawater solution (3.5wt% NaCl), and the light source is 1.0sun simulated sunlight. Within 4 hours, the hydrovoltaic power generation device can generate a DC voltage output of about -0.31V. Fig. 9 It is the hydrovoltaic electrical energy output of the single hydrovoltaic power generation device described in this example.
[0125] Example 6
[0126] In this embodiment, a hydrovoltaic power generation device based on cationic hydrogel is provided, and its preparation method is as follows: polyvinylidene fluoride (PVDF) is dissolved in dimethyl sulfoxide (DMSO) to prepare a solution with a concentration of 5wt%, and the aerogel solution is obtained after stirring evenly. 10wt% graphite powder is dispersed in the aerogel solution, and 4cm×2cm foam stainless steel electrodes are placed with a 2cm interval between the upper and lower parts in a unidirectional freezing mold. The above sol is poured into the mold, and then liquid nitrogen is frozen for 1 hour, exchanged in a deionized environment of 2-8 degrees for 48 hours, and then freeze-dried for 48 hours to obtain polyvinylidene fluoride (PVDF) aerogel; wherein the upper and lower foam stainless steel electrodes arranged in parallel are spaced 2cm apart and are respectively embedded in the aerogel, and the lower electrode and the bottom are spaced 2cm apart. 5wt% N-isopropylacrylamide (NIPAM), 0.05wt% N,N-methylenebisacrylamide (MBAA), 0.5wt% ammonium persulfate (APS), and 1wt% (3-acrylamidopropyl) trimethylammonium chloride (MPTAmC) were dissolved in deionized water to prepare NIPAM-MPTAmC solution. The aerogel was immersed in the NIPAM-MPTAmC solution and the solution was vacuum filtered. The aerogel filled with the hydrogel solution was cooled to 2-8°C. Under a nitrogen environment, the aerogel was immersed in a 0.7% tetramethylethylenediamine solution for cross-linking for 12h to cross-link the hydrogel internally. PVDF-PNIPAM-MPTAmC aerogel (named PPM) was obtained. The foam stainless steel electrode was connected to an external energy collection device through a wire to record the electrostatic energy generated by the separation of positive and negative ions in the solution inside the hydrovoltaic power generation device.
[0127] In this embodiment, the water sample is a simulated seawater solution (3.5wt% NaCl), and the light source is 1.0sun simulated sunlight. Within 4 hours, the hydrovoltaic power generation device can generate a DC voltage output of about -0.41V. Fig.10 It is the hydrovoltaic electrical energy output of the single hydrovoltaic power generation device described in this example.
[0128] As shown in Figures 9 and 10, Examples 5 and 6 involved are both cation-modified hydrogels. During the evaporation of seawater, the cation-modified hydrogel has positive charge, which promotes the transmission of anions and hinders the transmission of cations, resulting in the separation of positive and negative ions in the solution, with a large number of anions accumulating at the upper electrode and a large number of cations accumulating at the lower electrode. During the test, the positive electrode of the external energy collection device is connected to the upper electrode, and the negative electrode is connected to the lower electrode, thereby generating a negative potential difference.
[0129] Example 7
[0130] In this embodiment, a hydrovoltaic power generation device is provided, and its preparation method is as follows: poly (vinylidene fluoride - co - hexafluoropropylene) (PVDF-HFP) is dissolved in dimethyl sulfoxide to prepare a solution with a concentration of 5wt%, and the aerogel solution is obtained after stirring evenly. 5wt% amorphous carbon is dispersed in the aerogel solution, and 4cm×2cm foam copper electrodes are placed 5cm apart in a unidirectional freezing mold. The above sol is poured into the mold, and then liquid nitrogen is frozen for 1 hour, exchanged in a deionized environment of 2-8 degrees for 48 hours, and then freeze-dried for 48 hours to obtain poly (vinylidene fluoride - co - hexafluoropropylene) (PVDF-HFP) aerogel. The upper and lower foam copper electrodes arranged in parallel are spaced 5cm apart and are respectively embedded in the center of the aerogel, and the lower electrode and the bottom are spaced 2cm apart.
[0131] 10wt% N-isopropylacrylamide (NIPAM), 0.05wt% N,N-methylenebisacrylamide (MBAA), 0.5wt% ammonium persulfate (APS), and 1wt% 2-acrylamide-2-methylpropanesulfonic acid (AMPS) were dissolved in deionized water to prepare PNIPAM-AMPS solution. The aerogel was immersed in the PNIPAM-AMPS solution and the solution was vacuum filtered. The aerogel filled with the hydrogel solution was cooled to 2-8°C. In a nitrogen environment, the aerogel was immersed in a 5% tetramethylethylenediamine solution for cross-linking for 12h to cross-link the hydrogel internally. PNIPAM-HFP-AMPS-PVDF aerogel (named PH-AP) was obtained. The foam copper electrode was connected to an external energy collection device through a wire to record the electrostatic energy generated by the separation of positive and negative ions in the solution inside the hydrovoltaic power generation device.
[0132] In this embodiment, the water samples are deionized water, 3.5wt% sodium chloride solution, 10wt% sodium chloride solution, and 20wt% sodium chloride solution, and the light source is 1.0sun simulated sunlight. Fig.11 It is the hydrovoltaic power generation output of the hydrovoltaic power generation device in this example under different solvents. When the water sample is deionized, due to the small number of ions in the water sample, the voltage will rise first and then fall, and the maximum power generation can reach 0.168V. As the ion concentration increases, the maximum power generation gradually increases, and the water sample is 3.5wt% sodium chloride solution to reach 0.29V, and the water sample is 10wt% sodium chloride solution to reach 0.325V. When the ion concentration increases further, due to the excessive bottom ion concentration, the ion transmission efficiency decreases, and the maximum power generation decreases.
[0133] Example 8
[0134] In this embodiment, a microcrystalline hydrovoltaic power generation device is provided, and its preparation method is as follows: 2.5g of microcrystalline cellulose (MCC) is added to 50g of a solution containing NaOH (7 wt%) and dimethyl sulfoxide (10 wt%), and the cellulose powder is completely dissolved and then centrifuged (30min; 2500 rpm), a 4cm×2cm foam copper electrode is placed in a mold with a 3cm interval between the upper and lower parts, 5wt% of graphene is added to the supernatant, and the obtained supernatant is poured into the mold for sol gelation (5 h), and after the gel is complete, the gel material is washed with deionized water to obtain MCC hydrogel; finally, the MCC hydrogel is rapidly frozen and freeze-dried by liquid nitrogen (24 h) to obtain MCC aerogel. The upper and lower parallel foam copper electrodes are spaced 3cm apart and are respectively embedded in the center of the aerogel, and the lower electrode and the bottom are spaced 2cm apart.
[0135] 8wt% N-isopropylacrylamide (NIPAM), 0.05wt% N,N-methylenebisacrylamide (MBAA), 0.16wt% ammonium persulfate (APS), and 2-acrylamide-2-methylpropanesulfonic acid (AMPS) were dissolved in deionized water to prepare NIPAM-AMPS solution. The aerogel was immersed in the NIPAM-AMPS solution and the solution was vacuum filtered. The aerogel filled with the hydrogel solution was cooled to 2-8°C. Under a nitrogen environment, the aerogel was immersed in a 0.8wt% tetramethylethylenediamine solution for cross-linking for 12h to cross-link the hydrogel internally. MCC-PNIPAM-AMPS aerogel (named MPA) was obtained. The foam copper electrode was connected to an external energy collection device through a wire to record the electrostatic energy generated by the separation of positive and negative ions in the solution inside the hydrovoltaic power generation device.
[0136] Fig.12 The actual picture and ultraviolet spectrum of the water quality comparison before and after desalination of the hydrovoltaic power generation device described in this example can prove that the hydrovoltaic power generation device has the ability to desalinate water.
Claims
1. A hydrovoltaic power generation device, characterized in that: The hydrovoltaic power generation device comprises a gel composite material and an electrode. The gel composite material has a hydrophobic insulating porous material as a skeleton, and the skeleton is filled with an ionic thermosensitive hydrogel; wherein the ionic thermosensitive hydrogel is a hydrogel modified with anionic groups or cationic groups; wherein the hydrogel modified with anionic groups or cationic groups is a cross-linked hydrogel of a cationic modifier or an anionic modifier and a matrix material, wherein the mass ratio of the matrix material to the ionic modifier in the ionic thermosensitive hydrogel is 10:1 to 1:1; The matrix material includes one or more of poly N-isopropylacrylamide PNIPAM, poly N-vinylcaprolactam PNVCL, polysebacic anhydride PSPA, and poly N-acryloylglycineamide PNAGA; the anionic modifier includes at least one of 2-acrylamide-2-methylpropane sulfonic acid AMPS monomer and dimethylaminoethyl methacrylate DMAEMA; the cationic modifier includes at least one of (3-acrylamidopropyl)trimethylammonium chloride MPTAmC and dimethylaminopropylacrylamide DMAPAA.
2. The hydrovoltaic power generation device according to claim 1, characterized in that: The hydrophobic insulating porous material is a hydrophobic insulating porous material with a photothermal conversion function; the hydrophobic insulating porous material has vertically penetrating aerogel channels; The hydrophobic insulating porous material having a photothermal conversion function includes: a hydrophobic insulating porous material containing a photothermal functional filler or an intrinsic black hydrophobic insulating porous material without a photothermal functional filler; The photothermal functional filler includes one or more of carbon powder, carbon black, carbon nanotubes, graphene, graphite, amorphous carbon, MXene, metal organic framework MOF, and azobenzene; The mass percentage of the photothermal functional filler in the hydrophobic insulating porous material containing the photothermal functional filler is 1wt% to 10wt%.
3. The hydrovoltaic power generation device according to claim 2, characterized in that: The hydrophobic insulating porous material containing photothermal functional fillers includes: one or more of aerogels, foam plastics, and porous wood containing photothermal functional fillers; The aerogel is one or more of unmodified aerogel, hydrophobic and / or insulating modified aerogel; the foam plastic is one or more of unmodified foam plastic, hydrophobic and / or insulating modified foam plastic; the porous wood is one or more of unmodified porous wood, hydrophobic and / or insulating modified porous wood.
4. The hydrovoltaic power generation device according to claim 2, characterized in that: The intrinsic black hydrophobic insulating porous material without photothermal functional filler includes one or more of foam plastic and porous wood without photothermal functional filler; wherein the foam plastic is one or more of unmodified foam plastic and foam plastic modified by hydrophobicity and / or insulation; the porous wood is one or more of unmodified porous material and porous wood modified by hydrophobicity and / or insulation.
5. The hydrovoltaic power generation device according to any one of claims 3-4, characterized in that: The hydrophobic modification is one or more of surface micro-nano structure construction and surface hydrophobic coating processing; wherein the surface micro-nano structure construction method includes one or more of corrosion, etching, sol-gel method, and laser printing; wherein the surface hydrophobic coating processing includes one or more of surface coating and immersion treatment; wherein the material used for the surface hydrophobic coating processing includes one or more of fluorine-containing coating, silicon-containing coating, and fat chain-containing coating; The insulation modification is one or more of surface insulation treatment and impregnation insulation treatment; the material used for the insulation modification is at least one of organic insulation material, inorganic insulation material, and organic / inorganic composite insulation material; The organic insulating material is one or more of silicone resin, phenolic resin, epoxy resin, and polyimide; the inorganic insulating material is one or more of phosphate, silicate, TiO2, Cr2O3, MgO, ZrO2, SiO2, and Al2O3; the composite insulating material is one or more of SrTiO3 modified resin, SiO2 / SiC modified resin, Fe3O4 / SiO2 modified resin, and SiO2 modified resin.
6. A hydrovoltaic power generation device according to any one of claims 1 to 4, characterized in that: The preparation method of the gel composite material comprises: (1) mixing a base monomer, a cross-linking agent, an initiator, a modifier, and a solvent to obtain a mixed solution; (2) The hydrophobic insulating porous material is immersed in the mixed solution, vacuum filtered, cooled, and then immersed in the catalyst solution under protective gas conditions for cross-linking to obtain a gel composite material.
7. The hydrovoltaic power generation device according to claim 6, characterized in that: In the step (1), the matrix monomer is one or more of N-isopropylacrylamide NIPAM, N-vinylcaprolactam NVCL, sebacic anhydride SPA, and N-acryloylglycinamide NAGA; the crosslinking agent is N,N-methylenebisacrylamide MBAA; the initiator is ammonium persulfate APS; the solvent is deionized water; and the modifier is a cationic modifier or an anionic modifier; In the mixed solution of step (1), the monomer accounts for 3wt% to 10wt% of the solvent, the cross-linking agent accounts for 0.01wt% to 0.1wt% of the solvent, the initiator accounts for 0.1wt% to 1wt% of the solvent; and the modifier accounts for 0.3 to 10wt% of the solvent; In the step (2), the temperature is cooled to 2-8° C.; the protective gas is nitrogen; the catalyst is tetramethylethylenediamine TEDMA; and the concentration of the catalyst solution is 0.5 wt % to 1 wt %.
8. The hydrovoltaic power generation device according to claim 1, characterized in that: The electrodes include a positive electrode and a negative electrode; the electrodes are arranged on the gel composite material; wherein the positive electrode and the negative electrode are arranged in parallel; The electrode material is a porous electrode; wherein the porous electrode is a metal foam electrode or a graphite felt electrode; wherein the metal foam electrode includes one or more of a foam copper electrode, a foam stainless steel electrode, a foam iron-nickel electrode, a foam nickel electrode, a foam titanium electrode, and a foam aluminum electrode; The hydrovoltaic power generation device continuously outputs electrical energy during the evaporation process of the water body.
9. A method for preparing the hydrovoltaic power generation device according to claim 1, comprising: Mixing a base monomer, a cross-linking agent, an initiator, a modifier, and a solvent to obtain a mixed solution; The hydrophobic insulating porous material is immersed in a mixed solution, vacuum filtered, cooled, and then immersed in a catalyst solution under protective gas conditions for cross-linking to obtain a gel composite material, and electrodes are assembled to obtain a hydrovoltaic power generation device; Or the matrix monomer, cross-linking agent, initiator, modifier and solvent are mixed to obtain a mixed solution; the hydrophobic insulating porous material equipped with electrodes is immersed in the mixed solution, vacuum filtered, cooled, and then immersed in a catalyst solution under protective gas conditions for cross-linking to obtain a hydrovoltaic power generation device.
10. Application of the hydrovoltaic power generation device according to claim 1 or the hydrovoltaic power generation device prepared by the preparation method of the hydrovoltaic power generation device according to claim 9 in the fields of environment, new energy and renewable resources.
11. The use according to claim 10, characterized in that: The application in the environmental field includes one or more of seawater desalination, sewage treatment, distilled water collection, and plant bionic materials; The new energy field includes one or more of solar power generation and hydroelectric power generation; The renewable resource field includes one or more of plant growth monitoring, ecosystem services, ecosystem restoration, and water energy collection.
Citation Information
Patent Citations
Thermosensitive high strength and toughness nano-composite hydrogel and preparation method thereof
CN108794768A
Preparation method of efficient atmospheric water vapor adsorption composite material
CN116571219A